"I just like the stock": The role of Reddit sentiment in the GameStop share rally. Issue 1 (26th October 2022) - Long, Suwan (Cheng); Lucey, Brian; Xie, Ying; Yarovaya, Larisa
Abstract: This paper investigates the role played by the social media platform Reddit in the events around the GameStop (GME) share rally in early 2021. In particular, we analyze the impact of discussions on the r/WallStreetBets subreddit on the price dynamics of the American online retailer GameStop. We customize a sentiment analysis dictionary for Reddit platform users based on the Valence Aware Dictionary and Sentiment Reasoner (VADER) sentiment analysis package and perform textual analysis on 10.8 million comments. The analysis of the relationships between Reddit sentiments and 1‐, 5‐, 10‐, and 30‐min GameStop returns contribute to the growing body of literature on "meme stocks" and the impact of discussions on investment forums on intraday stock price movements.